INNOVATIVE TRANSFORMATION OF AGRICULTURAL ENTERPRISES IN CONDITIONS OF UNCERTAINTY - Yuliia Shevchenko (Izdevnieciba "Baltija Publishing", 2021)
The purpose of the paper is an in-depth study of the innovative transformation of agricultural enterprises in the conditions of unpredictability, the need to spread and introduce new technologies that help reduce the effects of any crisis. Methodology. The rationale for choosing the agricultural sector corporation survey is based on the use of market capitalization and share price statistics over the past ten years, which clearly demonstrate the stable, moderate economic development of the corporate system. The study of innovative projects allows to demonstrate the state of the innovation sector within corporations of agriculture and food industry. The results of the paper are to emphasize the importance of maintaining the technologically advanced sector of agriculture, which will reduce the financial, fixed and variable costs of the enterprise. Cooperation between corporations, research institutes and non-profit organizations in the field of innovation will be able to improve the economic development of the host countries and start a new stage in the functioning of TNCs in the field of agro-industrial complex. Although TNCs in the food industry have a low market capitalization compared to the technological sector of the economy, they are the basis of one of the components of sustainable development, namely the environmental component. Limited resources encourage their rational use and careful treatment. Practical implications. Demonstration of successfully implemented innovation projects in the future will stimulate the management staff of any enterprise, regardless of ownership, to the rational use of own resources and sustainable development. The market capitalization of TNCs in the agro-industrial sector proves that obtaining permanent profits can reduce the impact of economic, environmental and social crises. Crisis waves and peaks will be smoothed out. Value/originality. Solving the problem of overcoming the consequences of unpredictability through innovative projects emphasizes the importance of a deeper and more thorough study of vivid and real examples of the introduction of innovative products by well-known transnational corporations. The agro-industrial sector depends on the available technologies, as the preservation of natural resources, public health and food safety are the main areas of existence of this sector of the economy.